Changes in Corneal Curvature Value Before and After Phacoemulsification in Senile Cataract Patients: A case from Waled Regional Public Hospital, Cirebon - Nuruzzahrah, Naufarah; Piscaloka, Viora Rianda; Sisprihattono, Boyke (GHMJ (Global Health Management Journal), 2025)
Background: Cataract is the main cause of visual impairment and reversible blindness in the worldwide, especially in people over 50 years old. Cataract could be treated through cataract surgery, which one of the methods is phacoemulsification. Phacoemulsification has the advantage of reducing the risk of post-operative astigmatism due to its smaller incision compared to other techniques. Astigmatism was assessed by the curvature of the cornea, which measured using keratometry. Aims: To describe the differences in curvature cornea value pre and post phacoemulsification surgery in senile cataract patients at Waled Regional Public Hospital, Cirebon. Methods: This is a descriptive observational study. Sampling was obtained from medical records at Waled Regional Public Hospital. Data analysis using univariate analysis. Results: Subjects with preoperative keratometry difference (K1 and K2) of < 1 diopter (D) were 39 subjects (73.6%), and > 1 diopter (D) were 14 subjects (26.4%). Subjects with postoperative keratometry difference (K1 and K2) of < 1 diopter (D) were 38 subjects (71.7%), and > 1 diopter (D) were 15 subjects (28.3%). Subject who had reduction in corneal astigmatism were 21 subjects (39.6%), subject who did not have any change in corneal astigmatism were 14 subjects (26.5%), and subject who had increment in corneal astigmatism were 18 subjects (34%). Statistical analysis showed a p-value of 0.033, indicating a statistically significant change in corneal curvature value between before and after surgery (p-value = < 0.05). Conclusion: The results showed that out of 53 samples, most subjects had preoperative and postoperative astigmatism with a keratometry value difference (K1 and K2) of < 1 diopter (D). One month after phacoemulsification surgery, most samples showed a decrement in astigmatism compared to those who showed an increment in astigmatism.